Comparative transcriptomics of two coral holobionts collected during the 2017 El Niño heat wave reveal differential stress response mechanisms. (September 2022) - Ip, Jack Chi-Ho; Zhang, Yanjie; Xie, James Y.; Yeung, Yip Hung; Qiu, Jian-Wen
Abstract: Although coral species exhibit differential susceptibility to stressors, little is known about the underlying molecular mechanisms. Here we compared scleractinian corals Montipora peltiformis and Platygyra carnosa collected during the 2017 El Niño heat wave. Zooxanthellae density and chlorophyll a content declined and increased substantially during and after heat stress event, respective. However, the magnitude of change was larger in M. peltiformis . Transcriptome analysis showed that heat-stressed corals corresponded to metabolic depression and catabolism of amino acids in both hosts which might promote their survival. However, only M. peltiformis has developed the bleached coral phenotype with corresponding strong stress- and immune-related responses in the host and symbiont, and strong suppression of photosynthesis-related genes in the symbiont. Overall, our study reveals differences among species in the homeostatic capacity to prevent the development of the bleached phenotype under environmental stressors, eventually determining their likelihood of survival in the warming ocean. Graphical abstract: Unlabelled Image Highlights: Two coral species were sampled during the 2017 El Niño heat wave in Hong Kong. Montipora peltiformis was more susceptible than Platygyra carnosa. M. peltiformis and P. carnosa lost 90.2 % and 42.2 % of zooxanthellae, respectively. In both species, hosts responded more strongly to stresses than zooxanthellae. Stress and immune responses were stronger in M. peltiformis .